Sistem Pakar Mendiagnosa Penyakit Scabies (Rabi) Menggunakan Metode Ripple Down Rule - Vivian Fahmi Ritonga (STMIK Budi Darma, 2020)
Scabies is a type of disease caused by mites (Sarite) Sarcoptes scabies which is characterized by scab, baldness, and itching of the skin. This disease also spreads in a crowded environment of supporters, slums, environments with less hygiene scabies tend to be high in school-age children, adolescents and even adults. This is based on an interview with a dermatologist who said that, symptoms of scabies are itching between fingers and wrists itching on the outer surface of the elbows and when the disease is not cured, it can be an invection of the skin. Based on the above problems, it needs to be made an expert system that can help scabies and dermatologists in diagnosing scabies (Rabi). Because so far there has not been an application to handle this. The Ripple Down Rule method will calculate every symptom experienced by scabies by using the Ripple Down Rule calculation.